Perlindungan Hukum Terhadap Hak Pekerja Pada Pemutusan Hubungan Kerja Sepihak Oleh Perusahaan (Studi Putusan Nomor 361/PDT.SUS PHI/2023/PN.JKT.PST) - Muhammad Ramdhan Hananto; Gunardi Lie (UNES Law Review, 2024)
This research aims to analyze the legal protection of workers' rights in terminating employment relationships unilaterally by companies, with a focus on the case tried in Decision Number 361/PDT.SUS-PHI/2023/PN.JKT.PST. The research method used is normative juridical using Law Number 13 of 2003 concerning Employment, Law Number 2 of 2004 concerning Settlement of Industrial Relations Disputes, and Regulation of the Minister of Manpower and Transmigration of the Republic of Indonesia Number Per.31/MEN/XII/ 2008 as the main data source, supported by legal opinions in books and articles as secondary data sources. The results of the analysis show that legal protection for workers' rights in unilateral termination of employment has been clearly regulated in the applicable laws and regulations. However, in practice there are still violations committed by companies, such as not providing severance pay according to the provisions or not going through the regulated settlement procedures. Therefore, further efforts are needed to increase legal understanding for companies and workers, as well as more effective law enforcement to ensure better legal protection for workers' rights in situations of unilateral termination of employment. It is hoped that the results of this research can provide input for related parties in improving legal protection for workers in Indonesia.